Biofuels refining and performance (McGraw-Hill, 2008)
Learn about the ways to economically manufacture biofuels Written by a team of international experts, Biofuels Refining and Performance describes the refining processes and issues involved in producing fuel derived from recently living organisms or their by-products. Each chapter offers detailed discussion of theory as well as the actual experimental procedure used to economically manufacture biofuels on a commercial scale.